PERTIMBANGAN HUKUM DALAM PENETAPAN PERKARA PERMOHONAN ISBAT NIKAH DI PENGADILAN AGAMA - Dyanthi, Luh Merry; Suryana, I Nyoman (Universitas Mahendradatta, 2024)
The phenomenon of marriage of siri or marriage under the hands is still a lot happening among our society, whether done by ordinary people and figures known public. Issues surrounding siri marriage are still the subject of much discussion, especially if the practice is done by people who are well known by the community. In essence siri marriage from a religious perspective is valid, if the pillars and conditions are met. But in order to maintain order, the state has the right to regulate marriage matters, so marriage should be registered on the Registrar (for Muslims). For those who do not register their marriage, legally the marriage state is considered to have no legal force.